1995
DOI: 10.1002/j.1550-8528.1995.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Obese NIDDM and Nondiabetic Women: Short‐ and Long‐Term Weight Loss

Abstract: GUARE, JOHN C, RENA R WING AND AEDAMAR GRANT. Comparison of obese NIDDM and nondiabetic women: short-and long-term weight loss. Obes Res. 1995;3:329-335. Previous research suggests that overweight patients with diabetes lose less weight than nondiabetics. We compared the response of obese women with NIDDM to nondiabetic controls, matched for age and weight, to a behavior weight loss program. Forty-three overweight women (20 NIDDM, 23 nondiabetic) participated in the study. NIDDM and nondiabetic subjects were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
3
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 29 publications
5
65
3
5
Order By: Relevance
“…Prior studies of weight management programs for adults with diabetes 10,19 show that weight regain is common during a 1-year follow-up period; we found that more than one in six middle-aged adults with diabetes experienced weight loss and regain over 10 years.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Prior studies of weight management programs for adults with diabetes 10,19 show that weight regain is common during a 1-year follow-up period; we found that more than one in six middle-aged adults with diabetes experienced weight loss and regain over 10 years.…”
Section: Discussionmentioning
confidence: 48%
“…8,9 However, these studies are limited by relatively short periods of follow-up (1 and 3 years, respectively); thus, weight fluctuations 10 may not be well-detected. In addition, use of medical records rather than population-based data may not capture variations in demographically and geographically heterogeneous adults with diabetes.…”
mentioning
confidence: 99%
“…Although only moderate weight loss (5-10% of bodyweight) is required to improve glycaemic control, weight loss and maintenance of weight loss in patients with type 2 diabetes are generally more difficult than in non-diabetic individuals. 8,43 Furthermore, most antidiabetic medications (in particular sulphonylureas, thiazolidinediones, and insulin) produce concomitant weight gain. 5,31,44 In this study, a mean weight loss of 6·1 kg was noted in patients who completed the 1-year treatment with 20 mg/day rimonabant, much the same as that described in the Diabetes Prevention Program (DPP), 45 in which patients were treated with an intensive lifestyle intervention.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Thus, pharmacological support for weight loss may be particularly appropriate in the diabetic population. Subjects were predominantly normotensive and normolipidemic at baseline.…”
Section: Discussionmentioning
confidence: 99%